1997
DOI: 10.1007/s12144-997-1005-0
|View full text |Cite
|
Sign up to set email alerts
|

Impulsivity, fight history, and camaraderie as predictors of a willingness to escalate a disturbance

Abstract: This field study examined the relationships between six predictor variables and a self-report measure of spectators' likelihood of joining in a crowd disturbance. Subjects were males (N = 78) found in attendance at an ice hockey game. The variables related to the likelihood of escalating a disturbance included subjects who were more impulsive, had a history of fighting, were younger, saw provocations as more volatile, liked to watch player fights and attended with others. A multiple regression analysis yielded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
17
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 17 publications
(26 reference statements)
4
17
1
Order By: Relevance
“…It is also consistent with previous results showing that both trait aggression [Russell, 1995;Russell and Arms, 1995;Wilkins et al, 19741 and subjects' records of previous aggression [Arms and Russell, 1996;Hartmann, 19691 predict to the likelihood of their involvement in future violence.…”
Section: Resultssupporting
confidence: 92%
“…It is also consistent with previous results showing that both trait aggression [Russell, 1995;Russell and Arms, 1995;Wilkins et al, 19741 and subjects' records of previous aggression [Arms and Russell, 1996;Hartmann, 19691 predict to the likelihood of their involvement in future violence.…”
Section: Resultssupporting
confidence: 92%
“…In regard to the relationship between impulsivity and aggression, Wheeler and Caggiula (1966) found that high-impulsive participants exhibited more aggression than low-impulsive participants following exposure to aggressive models, suggesting that impulsive individuals have lower inhibitions against violating social norms. Building on this work, research with hockey spectators found a strong connection between impulsivity and willingness to escalate in disturbance (Arms & Russell, 1997). In fact, "impulsive aggression" is considered a common type of aggression whereas individuals engage in aggressive behaviors that were not premeditated (Anderson & Huesmann, 2007), making impulsive individuals more likely to engage in such types of aggression.…”
Section: Impulsivity and Fan Aggressionmentioning
confidence: 89%
“…However, when it comes to aggression by sports spectators, individual-difference variables are often overlooked; researchers acknowledge that such variables could be important predictors of spectator aggression and call for research to incorporate them (Dimmock & Grove, 2005). Specific factors along those lines include self-esteem, impulsivity, and overall tendencies regarding verbal aggression and physical aggression (Arms & Russell, 1997;Dimmock & Grove, 2005;Russell & Arms, 1995.…”
Section: Self-esteem and Fan Aggressionmentioning
confidence: 99%
“…Previous research has shown that self-reported involvement in riots surrounding sports events is associated with physical aggressiveness and higher levels of anger as measured by the Aggression questionnaire (Buss & Perry, 1992), and that rioters show higher levels of impulsiveness, sensation seeking and psychopathy (see Mustonen, Arms, & Russell, 1996;Russell, 2004;Russell & Arms, 1998). Moreover, individuals with a personal history of violence are more likely to allow a disturbance to escalate into a full-blown riot (Arms & Russell, 1997). Neither the aforementioned broadband personality dimensions nor the MCAA were used as predictors in previous studies on football hooliganism.…”
Section: Applications Of the Individual Differences Approach To Hoolimentioning
confidence: 99%